1976
DOI: 10.1159/000144670
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of articular cartilage of achondroplastic mice

Abstract: Articular chondrocytes of achondroplastic mice (cn/cn) resemble ultrastructurally those of their non-achondroplastic siblings (Cn/Cn or Cn/cn), except for premature deposition of glycogen and a tendency to undergo regression. The latter may be slight or extreme. The ultimate cause of the vulnerability of the chondrocytes and the cause of the heterogeneity of the reaction could not be determined with the method employed. Nevertheless, increased vulnerability accounts for cell death under conditions which are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In some cases among the mitochondria of a usual appearance there appear also small amounts of mitochondria with a strikingly light matrix and slightly damaged cristae. They are probably disintegrating mitochondria as was also stated by Kaplan and Meyer (1959), Meachim et al (1965), Weiss and Mirrow (1972), Ghadially et al (1970), Mitchell and Shepard (1970), Dearden et al (1974), Gritzka et al (1974), Refior (1974), Rother and Redel (1975), Hanaoka (1976), Podrushniak and Cerkasov (1976), Silberger et al (1976), and others especially on the basis of investigations of these organelles in ageing cartilage and initial forms of arthroses. Ri b 0 so m es in the cytoplasm of chondrocytes of the superficial layer are mostly bound to membrane of the granular endoplasmic reticulum.…”
Section: B) Cytoplasmmentioning
confidence: 56%
“…In some cases among the mitochondria of a usual appearance there appear also small amounts of mitochondria with a strikingly light matrix and slightly damaged cristae. They are probably disintegrating mitochondria as was also stated by Kaplan and Meyer (1959), Meachim et al (1965), Weiss and Mirrow (1972), Ghadially et al (1970), Mitchell and Shepard (1970), Dearden et al (1974), Gritzka et al (1974), Refior (1974), Rother and Redel (1975), Hanaoka (1976), Podrushniak and Cerkasov (1976), Silberger et al (1976), and others especially on the basis of investigations of these organelles in ageing cartilage and initial forms of arthroses. Ri b 0 so m es in the cytoplasm of chondrocytes of the superficial layer are mostly bound to membrane of the granular endoplasmic reticulum.…”
Section: B) Cytoplasmmentioning
confidence: 56%
“…Changes in morphology of articular cartilage are associated, to a major extent, with age (except for species-related changes). Such changes have been reported for instance in adult mice (Silberger et al 1976), rabbits (Barnett et al 1963; Davies et al …”
mentioning
confidence: 62%
“…Changes in morphology of articular cartilage are associated, to a major extent, with age (except for species-related changes). Such changes have been reported for instance in adult mice (Silberger et al 1976), rabbits (Barnett et al 1963; Davies et al 1962), dogs (Lust et al 1972;Lust and Sherman 1973;Wiltberger and Lust 1975), cattle (Horky 1983(Horky , 1984 and man (Ghadially and Roy 1969;Ghadially 1978Ghadially , 1982Horky 1980) and to some extent in pigs (Grondalen 1974c, f;Nakano et al 1979a, b). However, only the work by Bhatnagar et al (1981) has been concerned with the ultrastructure of porcine articular cartilage in the postnatal period.…”
Section: Ultrastructure Porcine Articular Cartilage Developmentmentioning
confidence: 85%
“…It functions as a lubricated surface for articulation by reducing friction and facilitating the transmission of loads. Study of cartilage-related diseases showed that the abnormal changes in morphology and function of cartilage are associated with various pathologies, such as osteoarthritis, achondroplasia and costochondritis [1][2][3][4][5][6]. Chondrocytes, the only resident cells in healthy cartilage, are responsible for the production and maintenance of the cartilaginous tissue.…”
Section: Introductionmentioning
confidence: 99%